Perancangan Workshop FFWD dan Catalyst Development Program di PT.X. - Kevin Widjaja; Felecia Felecia (Jurnal Titra, 2018)
Human Resources (HR) in PT. X has started to implement FFWD method (a new way of working) less than 1 year, since the third quarter in 2017. That is why PT.X needs to execute the training for their employees so they know what is Fastforward and make some system that is called Catalyst Development Program for doing tracking and appreciate the Catalyst. Before this, there is already a workshop for a high level employee, now PT.X needs the workshop for middle level employee. The result of the workshop design that can be use for middle level employee is the result from modification and improvement from the last workshop. Catalyst Development Program that has been created is transactional where Catalyst will get the reward in a form of material.